Acts and Laws of His Majesty’s Province of New Hampshire 9–10 (1771), ch. 6, § 2 - (:unkn) unknown (General Publisher, 1771)
Prohibited gathering in numbers of twelve or more and being armed with clubs and other weapons, or any group numbering thirty or more, from unlawfully, riotously, or tumultuously assembling
--
Keywords: CARRY - INTENT TO COMMIT CRIME